2013
DOI: 10.1057/ejdr.2013.26
|View full text |Cite
|
Sign up to set email alerts
|

Cooperation in International Strategic Alliances and Impact on Host Economies: Knowledge Transfer and Diffusion to Local Firms

Abstract: Researchers have suggested that linkages between multinational enterprises entering developing countries and local firms can promote knowledge upgrading in local firms. Alliances are a particularly intense type of linkage, and this study investigates how the construct of cooperation, which is the essence of alliance activity, relates to knowledge transfer from foreign to local alliance partners, and then to how large a proportion of that knowledge is subsequently diffused to other local firms. The results sugg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
4
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 48 publications
0
4
0
1
Order By: Relevance
“…As to the recent literature about international strategic alliance, the current research can communicate with strategic alliance as a key for small business go international (Haase and Franco, 2015), especially with multinational enterprises from emerging markets (Chiao et al , 2010), as international strategic alliance can complement the lake of resources (Shi et al , 2014). Learning and knowledge transfer are the main motivations of international strategic alliance (Christoffersen, 2013), and the current research further explores the different kinds of knowledge and different resources required by Taiwanese and Russian partners. Mutual commitment of the alliance partners is also the main determinants of the success in strategic alliances (Aldakhil and Nataraja, 2014; Lin and Guan, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…As to the recent literature about international strategic alliance, the current research can communicate with strategic alliance as a key for small business go international (Haase and Franco, 2015), especially with multinational enterprises from emerging markets (Chiao et al , 2010), as international strategic alliance can complement the lake of resources (Shi et al , 2014). Learning and knowledge transfer are the main motivations of international strategic alliance (Christoffersen, 2013), and the current research further explores the different kinds of knowledge and different resources required by Taiwanese and Russian partners. Mutual commitment of the alliance partners is also the main determinants of the success in strategic alliances (Aldakhil and Nataraja, 2014; Lin and Guan, 2015).…”
Section: Discussionmentioning
confidence: 99%
“…Their results indicated the positive influence of both intellectual capital and experience on value creation. Christoffersen (2013a) suggested that ISAs have a strong positive impact on knowledge transfer from foreign to local partners, but not to competitors, suppliers, or customers. Nakos et al (2014), however, concluded that alliances between competitors tend to offer redundant knowledge.…”
Section: Outcome Of Isasmentioning
confidence: 99%
“…Si se hace un resumen de las investigaciones realizadas en el tópico de alianzas estratégicas, se identifica que una gran parte se han centrado en las fases previas y posteriores de los acuerdos, incluidos los motivos de colaboración, la selección, la internacionalización, las negociaciones de los socios, los contratos y los tipos de alianzas (Doz, 1996;Doz et al, 2000;Glaister & Buckley, 1996;Parkhe, 1993aParkhe, , 1993bYang, 2020). Otra parte de las investigaciones, en las últimas dos décadas, se han centrado en aspectos relativos a su implementación, especialmente a lo relacionado con el logro de los objetivos de la alianza (Banal-Estañol et al, 2017;Brouthers & Bamossy, 2006;Christoffersen, 2013a;Dubrovski, 2016;Frankort et al, 2016;Huang, 2017;Lee et al, 2013;Luo, 2001;Panico, 2017;Reuer & Ariño, 2002). Hay que mencionar que, a pesar de la gran cantidad de investigaciones realizadas sobre este tema, quedan varios aspectos relacionados sobre su concepto por discernir.…”
Section: Introductionunclassified